Sosialisasi Penggunaan AI dalam Proses Belajar Mengajar di SMK Negeri 4 Padangsidimpuan - Lela Budiarti; Alwendi Alwendi (Jurnal Pelayanan Masyarakat, 2025)
The development of artificial intelligence (AI) technology offers new opportunities to enhance the effectiveness of teaching and learning processes. However, the level of understanding and utilization of AI in vocational school environments remains varied. The socialization activity on the use of AI at SMK Negeri 4 Padangsidimpuan was carried out as an effort to improve digital literacy, pedagogical competence, and the skills of both students and teachers in effectively utilizing AI technology. The activity methods included material presentation, demonstrations of educational AI applications, and hands-on practice using several AI platforms for material creation, data analysis, and learning support. The results showed an improvement in teachers' and students' understanding of basic AI concepts, their ability to use AI tools in teaching, and increased motivation to integrate AI into the learning process. This socialization activity is expected to serve as an initial step in developing an adaptive, innovative, and technology-based learning ecosystem that aligns with the needs of the digital era.